Advances in Oral Solid Drug Delivery Systems: Quality by Design Approach in Development of Controlled Release Tablets - Prachi Atre; Syed A. A. Rizvi (BioChem, 2025)
Oral solid drug delivery continues to be the gold standard in pharmaceutical formulations, owing to its cost-effectiveness, ease of administration, and high patient compliance. Tablets, the most widely used dosage form, are favored for their precise dosing, simplicity, and economic advantages. Among these, controlled release (CR) tablets stand out for their ability to maintain consistent drug levels, enhance therapeutic efficacy, and reduce dosing frequency, thereby improving patient adherence and treatment outcomes. A well-designed CR system ensures a sustained and targeted drug supply, optimizing therapeutic performance while minimizing side effects. This review delves into the latest advancements in CR formulations, with a particular focus on hydrophilic matrix systems, which regulate drug release through mechanisms such as swelling, diffusion, and erosion. These systems rely on a variety of polymers as drug-retarding agents to achieve tailored release profiles. Recent breakthroughs in crystal engineering and polymer science have further enhanced drug solubility and bioavailability, addressing critical challenges associated with poorly soluble drugs. In terms of manufacturing, direct compression has emerged as the most efficient method for producing CR tablets, streamlining production while ensuring consistent drug release. The integration of the Quality by Design framework has been instrumental in optimizing product performance by systematically linking formulation and process variables to patient-centric quality attributes. The advent of cutting-edge technologies such as artificial intelligence and 3D printing is revolutionizing the field of CR formulations. AI enables predictive modeling and data-driven optimization of drug release profiles, while 3D printing facilitates the development of personalized medicines with highly customizable release kinetics. These innovations are paving the way for more precise and patient-specific therapies. However, challenges such as regulatory hurdles, patent constraints, and the need for robust in vivo validation remain significant barriers to the widespread adoption of these advanced technologies. This succinct review underscores the synergistic integration of traditional and emerging strategies in the development of CR matrix tablets. It highlights the potential of hydrophilic and co-crystal matrix systems, particularly those produced via direct compression, to enhance drug bioavailability, improve patient adherence, and deliver superior therapeutic outcomes. By bridging the gap between established practices and innovative approaches, this field is poised to address unmet clinical needs and advance the future of oral drug delivery.